Gerakan Pengelolaan Sumber Daya Manusia Untuk Meningkatkan Pendidikan Di Era Covid-19 - Elex Sarmigi (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2022)
The entry of the Covid-19 virus into Indonesia in early 2020 had a negative impact, especially in the world of education. Several times the government's policy to impose a lockdown to reduce activities outside the home has an impact on the delay in the education process in schools. Therefore, the purpose of this service is to help school-age children and the community in Koto Majidin Mudik Village to continue to receive education during this pandemic. This activity was carried out with the help of Religious Competency-Based Real Work Lectures (KKN-BKK) IAIN Kerinci in 2021. The programs implemented were 1) Study Guidance, 2) Healthy Gymnastics, 3) Fajr Education, and 4) Maghrib Koran.